2009
DOI: 10.1097/ijg.0b013e318170a747
|View full text |Cite
|
Sign up to set email alerts
|

Intracameral Bevacizumab (Avastin) for Neovascular Glaucoma

Abstract: ICB resulted in a rapid regression of the iris and angle neovascularization, which permitted to halt the progression of PAS process. This pilot study shows that intracameral injection of bevacizumab may be a helpful adjunct for the surgical treatment of NVG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 9 publications
0
39
1
2
Order By: Relevance
“…The extent of NVI was graded as grade I (1/4 iris surface), grade II (2/4 iris surface), grade III (3/4 iris surface), and grade IV (all iris surface). 11 Gonioscopy was performed before trabeculectomy in the majority of patients. Very high IOP with corneal epithelial edema in some cases obscured iris and angle neovascularization, limiting gonioscopic data.…”
Section: Additional Glaucoma Surgeriesmentioning
confidence: 99%
“…The extent of NVI was graded as grade I (1/4 iris surface), grade II (2/4 iris surface), grade III (3/4 iris surface), and grade IV (all iris surface). 11 Gonioscopy was performed before trabeculectomy in the majority of patients. Very high IOP with corneal epithelial edema in some cases obscured iris and angle neovascularization, limiting gonioscopic data.…”
Section: Additional Glaucoma Surgeriesmentioning
confidence: 99%
“…1,[13][14][15] In most of these case reports, previous or concomitant PRP was applied, limiting extrapolation of the duration of isolated bevacizumab effect. 16,17 Duch et al 16 studied the use of intracameral bevacizumab (ICB) in 6 patients with NVG as the first maneuver before PRP and/ or filtering surgery. ICB resulted in a marked regression of anterior segment neovascularization with intraocular pressure (IOP) control without filtering surgery in 2 cases.…”
mentioning
confidence: 99%
“…9,10,18,19 In addition, other studies show that intracameral bevacizumab injections also have an effect on iris rubeosis and neovascularization regression and a supposed effect on IOP reduction. [20][21][22] However, in cases with severe peripheral anterior synechiae (more than 270 degrees), bevacizumab injection alone might not be enough to decrease IOP in NVG and a surgical option is needed. 23 Kim et al 4 reported that VEGF concentration in the aqueous humor is different between the success group and the failure group of Ahmed valve implantation.…”
Section: Resultsmentioning
confidence: 98%